Exploring the Potential Alignment between VR/AR and Universal Design for Learning for Mathematics Accessibility in Elementary Schools: A Systematic Literature Review - Aryanti, N. Sinta Mustika; Munir; Famelia; Yunita, Septi (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Mathematics instruction in elementary schools often presents accessibility challenges, particularly for learners who struggle with abstract and symbolic concepts. Universal Design for Learning (UDL) provides a flexible framework to support diverse learners through multiple means of representation, engagement, and expression. In addition, immersive technologies such as Virtual Reality (VR) and Augmented Reality (AR) offer opportunities to visualize mathematical concepts and create interactive learning experiences. This study aims to explore the potential alignment between VR/AR and UDL in improving accessibility in elementary mathematics learning. A systematic literature review of studies published between 2015 and 2024 was conducted, involving eight empirical studies analyzed through thematic synthesis. The findings show that VR/AR can support conceptual understanding, increase student engagement, and provide multiple ways for students to express their understanding. This study contributes to understanding how immersive technologies can support UDL principles in mathematics learning. The findings also suggest that teachers can use VR/AR to design more inclusive learning experiences, supported by adequate training and infrastructure. However, challenges such as limited devices, teacher readiness, and technical constraints need to be considered in implementation.